THE RELATIONSHIP BETWEEN WEIGHT INCREASES WITH UPPER ARM CIRCUMFERENCE AMONG THIRD TRIMESTER PREGNANT WOMEN IN YOGYAKARTA, INDONESIA - Utami, Deby Kurnia; Lestari, Pratiwi Puji; Pratiwi, Ajeng Maharani (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The incidence of Indonesian pregnant women who suffer from Chronic Energy Deficiency (CED) reached 21.6%. In Yogyakarta, the presentation of CED reached 22.69%. Chronic Energy Shortage (CES) is mainly caused by nutrient intake imbalance that influences the weight gain in pregnant women. Aims: This is to knowrelationships between body weights among third-trimester pregnant women with their upper arm circumference. Methods: The study was a quantitative analytical study with cross-sectional approach. This research employed an accidental sampling method to select the 40 third-trimester pregnant women who visited health Centre in Yogyakarta. The data was then analysed using Chi Square test. Results: There was a significant relationship between weight gain with upper arm circumference among third-trimester pregnant women (pvalue = 0.012). As a note that, the weight gain of the participated pregnant women and their size upper arm circumference were in the regular group. Conclusion: The significant relationship between weight gain and higher arm circumference among third-trimester pregnant women alarm the needs to provide an advice for nutrition intake balance during pregnancy in Yogyakarta.Â